2015
DOI: 10.1016/j.firesaf.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of protected beams and their connections on the fire resistance of composite buildings

Abstract: According to full-scale fire tests, it is noticed that tensile membrane action within the concrete floor slabs plays an important role in affecting the fire resistance of composite buildings. It is well known that the development of tensile membrane actions relies on the vertical support along the edges of the slab panel. However, there is at present a lack of research into the influence of vertical supports on the tensile membrane actions of the floor slabs. In this paper, the performances of a generic three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Many theoretical models have been adopted to represent the material behavior of steel and concrete at elevated temperature. In this study, the Eurocode was selected because it is widely used and has been validated by many researchers (Memari et al, 2014;Lin et al, 2015;Selamet and Bolukbas, 2016;Jiang and Li, 2018).…”
Section: Materials Behavior At Elevated Temperaturementioning
confidence: 99%
“…Many theoretical models have been adopted to represent the material behavior of steel and concrete at elevated temperature. In this study, the Eurocode was selected because it is widely used and has been validated by many researchers (Memari et al, 2014;Lin et al, 2015;Selamet and Bolukbas, 2016;Jiang and Li, 2018).…”
Section: Materials Behavior At Elevated Temperaturementioning
confidence: 99%
“…The analyses also demonstrated that the surrounding cool structure can improve the fire resistance of the fire compartment. Lin et al [18] investigated the effect of protected beams on the fire resistance of composite buildings. They compared the behaviour of the composite floor with fixed and non-fixed vertical support on the protected steel beams at the perimeter of the slab panel.…”
Section: Figure 1: Tensile Membrane Action Mechanismmentioning
confidence: 99%
“…They also proposed a simplified method to calculate the non-linear characteristics of composite connections in the analysis of beam catenary action at high temperatures, which was validated against their experimental results. Lin et al [14] used 2-noded connection elements representing end-plate and partial-depth endplate connections in their high-temperature 3-D composite floor model to take into account of the impact of connections on the 3-D behaviour of composite floors in fire. Selamet et al [15] modelled a composite steel-framed floor system with beam-to-beam shear connections at elevated temperatures and found that the connection reaches its axial and rotational capacities during the fire cooling phase, leading to the failure of bolts caused by combined shear and tension.…”
Section: Introductionmentioning
confidence: 99%